Antioxidants may Attenuate Plasma Erythropoietin Decline after Hyperbaric Oxygen Diving - Mutzbauer, Till Sebastian (International journal of sports medicine, 2015)
According to previous studies, plasma erythropoietin (EPO) may decrease after hyperbaric oxygen exposure due to oxidative stress. It is hypothesized that the decrease of EPO can be attenuated by oxygen free radical scavengers. The aim of the present study was to evaluate whether EPO plasma levels can be influenced by oral application of vitamin C and E before repeated hyperbaric oxygen exposure during diving. 16 healthy male police task force divers performed 3 morning dives on oxygen within a regular diving schedule on 3 consecutive days. They were randomized into either the placebo group or the vitamin group, receiving 1 g ascorbic acid and 600 IU D-α-tocopherol orally 60 min before the dive. Blood samples for EPO measurement were taken on days 1, 2, and 3 at T1, T3 and T5 60 min before and at T2, T4 and T6 60 min after each dive, respectively. A moderate decrease of EPO was observed beginning at T3 until T6 in the placebo group. The EPO concentrations in the vitamin group did not show relevant variations compared to baseline. Radical scavenging vitamins C and D may counteract hyperbaric oxygen related mechanisms reducing EPO production in hyperbaric oxygen exposure during diving.
Gesehen am 10.08.2020